Does giant breast tumour have an increased complication risk for subcutaneous mastectomy and reconstruction? - Yusuf, Kenan Coban; Nazim, Gumus (Indian Journal of Plastic Surgery, 2006)
Prosthetic breast reconstruction after subcutaneous mastectomy has some complications such as skin necrosis, loss of areola-nipple, haematoma, seroma, infection, displacement of implants, areola nipple disposition and inadequate skin construction resulting in skin wrinkles. We discuss whether giant breast tumour has an increased complication risk after the surgery, in this paper which reports a patient with giant breast tumour i.e., a large recurrent fibroadenoma in the same breast. Subcutaneous mastectomy was performed without skin reduction through submammary incision. Total muscular coverage was provided for immediate reconstruction using 350 cc gel- filled breast implant. Though haematoma or seroma didn′t exist, superficial skin necrosis developed subsequently. Spontaneous epithelisation was observed all of the necrosis area to cover this area in a few weeks. Initially, skin coverage and areola nipple position on the breast was acceptable, but 8 months after the operation, skin reconstruction was not good enough to provide good skin envelope. Just as as skin lack or insufficiency is a severe problem in breast reconstruction, excess skin may be another trouble for providing an acceptable breast shape.
Keywords: Breast reconstruction; giant breast tumour; implant; skin excess; wrinkles